Determining Association of Myopia and Primary Open Angle Glaucoma - Admani, Mohammad Uzair; Maree, Ghazi Khan; Mirza, Azfar Ahmed; Rajput, Arsalan Ahmed; Mahesar, Mona Liza; Munawar-Ul-Islam, Sanam; Shaikh, Adil Ali; Zeba, Nudrat (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the association between myopia and primary open-angle glaucoma. Study Design: Comparative cross-sectional study. Place and Duration of Study: Department of Ophthalmology, Liaquat University Hospital Jamshoro from Jan to Jun 2015. Methodology: A sample of 170 diagnosed cases of myopia and 170 subjects without myopia were selected. Inclusion criteria were age 35-60 years, both genders, cases with myopia >1.0 D and controls - without myopic error. Visual status was determined by the Huwitz autorefractor (model 8800) machine. Retinoscopy, Goldmann’s Applanation tonometry, gonioscopy, vertical cup to disc (VCD) ratio and visual field defects were detected. Results: Age of group – 1 and–2 was 55.7 ± 8.6 and 52.3 ± 7.3 years respectively (p=0.071). VCD ratio in group-1 was 0.6 ± 0.13 compared to 0.5 ± 0.02 in group-2 (p<0.001). Normal and abnormal VCD ratio in cases and control was noted as 161 (94.7%) vs. 168 (98.8%) and 9 (5.2%) vs. 2 (1.1%) respectively (p<0.03). 23 (13.5%) of group–1 show visual field defects compared to 6 (3.5%) in group–2. Intraocular pressure was found elevated in group-1 16.8 ± 2.3 mmHg compared to 14.0 ± 2.7 in group-2 (p<0.001). POAG was observed in 9 (5.2%) myopes group–1 compared to 2 (1.1%) in group–2 (p<0.003). Conclusion: The present study concludes that myopia is associated with primary open-angle glaucoma, and the risk of glaucoma is high in these patients.